Upaya Pembina Panti Asuhan Dalam Mengatasi Kenakalan Remaja Di Panti Asuhan Aisyiyah Putri Bukittinggi - Annisa Novia; Yeni Afrida; Riza Sri Putri (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Juveniles between the ages of 12 and 21 who engage in activities that have the potential to harm others and cause a commotion in society are considered juvenile offenders. The purpose of this study is to know how what efforts should be taken by orphanage managers and coaches to overcome adolescent bad behavior is the purpose of this study. This study used a qualitative approach to collect data through observation, interviews, and documentation. The factors behind the bad behavior of adolescents start from the lack of parental discipline and the destruction of households which are the root of the problem of many children in orphanages. The results of this study make it clear that fostering religious knowledge is one way that can be done by caregivers and administrators of the Aisyiyah Putri Bukittinggi Orphanage to eradicate juvenile delinquency. Therefore, a person can behave better if he is more deeply immersed in his religion. The study's conclusion was that caregivers and orphanage coaches can take care of children without biological parents by acting in those roles. The orphanage strives to ensure that orphanage children get a good education to prevent juvenile crime that disturbs the surrounding community.